Relationship between parents' child rearing style and emotion-regulation skills in adolescents: moderating role of parenting stresses - Mahdi Kheradmand; Raoofeh Ghayoomi; Toktam Ghahreman; Shahrbanoo Ghahari (Social Determinants of Health, 2018)
Background: Adolescence is one of the most challenging periods in the life of humans during which the individual is faced with personal, social, occupational, and family problems as well as extensive physical and cognitive changes. Dealing with these problems and changes requires emotional regulation and management. Parents play a vital role in adolescences' coping styles with the mentioned problems and emotions. Hence, the present study aimed at examining the moderating role of parenting stress in the relationship between child rearing style and emotion regulation skills in adolescents.